PMP Certification - Chandramouli, Subramanian (Pearson Education India, 2019)
Project Management Professional (PMP®) is a credential oered by the Project Management Institute (PMI®). Both government and private organizations employ PMP® certied project managers in an attempt to improve the success rate of projects in all areas.